Predicting online product sales via online reviews, sentiments, and promotion strategies - Chong, Alain Yee Loong; Li, Boying; Ngai, Eric W.T.; Ch'ng, Eugene; Lee, Filbert (Emerald Group Publishing Limited, 2016)
Purpose – The purpose of this paper is to investigate if online reviews (e.g. valence and volume), online promotional strategies (e.g. free delivery and discounts) and sentiments from user reviews can help predict product sales.